This action might not be possible to undo. Are you sure you want to continue?
5 Sequences
Let (X, d) be a metric space. A sequence in X is a function from N to X.
If ϕ : N → X is a sequence we write
(x
n
), (x
n
)
n∈N
or (x
0
, x
1
, . . .)
for ϕ, where x
n
= ϕ(n) is the nth term of the sequence ϕ = (x
0
, x
1
, . . .).
Sequences in R are called real sequences.
Deﬁnition 5.1. A sequence (x
n
) in X converges to x if for every neighbor
hood U of x there exists N ∈ N such that
x
n
∈ U for all n ≥ N.
In this case we write
x
n
→ x or lim
n→∞
x
n
= x or lim
n
x
n
= x.
A sequence (x
n
) which does not converge is called divergent.
Proposition 5.2. The following are equivalent.
(i) lim
n
x
n
= x.
(ii) For every ε > 0, there is N ∈ N such that x
n
∈ B(x, ε) for all n ≥ N.
(iii) For every ε > 0, there is N ∈ N such that d(x
n
, x) < ε for all n ≥ N
Proposition 5.3. (i) (Uniqueness of the limit) A sequence cannot have
more than one limit.
(ii) (Boundedness) If (x
n
) converges to x, then there is r > 0 such that
x
n
∈ B
r
(x).
Proof of (ii). Assume that (x
n
) converges to x. By (iii) of the previous
proposition with ε = 1, there is N so that x
n
∈ B
1
(x) for all n ≥ N. Now
take r be any number bigger or equal to d(x
1
, x), . . . , d(x
N−1
, x) and 1. Then
x
n
∈ B
r
(x) for all n, as claimed.
Deﬁnition 5.4. Let ϕ = (x
n
) be a sequence in X and let φ : N → N be a
strictly increasing function. Then ϕ ◦ φ : N → X is called a subsequence of
ϕ = (x
n
).
We write (x
n
k
) for the subsequece ϕ ◦ φ where φ(k) = n
k
. Since ψ is
strictly increasing n
1
< n
2
< n
3
< . . ..
20
Proposition 5.5. If (x
n
) is a convergent sequence with limit x, then every
subsequence (x
n
k
) of (x
n
) converges to x.
Proof. Let (x
n
k
) be a subsequence of (x
n
). Take a neighborhood U of x.
Since limx
n
= x, there is N ∈ N such that x
n
∈ U for all n ≥ N. From the
deﬁnition of a subsequence, n
k
≥ k for all k ∈ N. So, n
k
≥ N for all k ≥ N.
Thus x
n
k
∈ U for all k ≥ N. Hence (x
n
k
) converges to x as claimed.
Deﬁnition 5.6. A sequence (x
n
) in a metric space (X, d) is said to be
Cauchy if for every ε > 0, there exists N such that
d(x
n
, x
m
) ≤ ε for all n, m ≥ N.
Proposition 5.7. Let (X, d) be a metric space.
(i) Every Cauchy sequence is bounded.
(ii) Every convergent sequence in X is Cauchy.
Proof of (ii). Assume that (x
n
) converges to x. Then, given ε > 0, there
is N such that
d(x
n
, x) < ε/2 for all n ≥ N..
Hence
d(x
n
, x
m
) ≤ d(x
n
, x) +d(x, x
m
) < ε/2 +ε/2 = ε
for all n, m ≥ N. So, (x
n
) is a Cauchy sequence as claimed.
5.1 Real sequences
Proposition 5.8. Let (x
n
) and (y
n
) be convergent sequences in R and let
α ∈ R. Then
(i) The sequence (x
n
+y
n
) converges and lim(x
n
+y
n
) = limx
n
+limy
n
.
(ii) The sequence (αx
n
) converges and lim(αx
n
) = αlimx
n
.
Proof of (i). Take ε > 0. Since (x
n
) and (y
n
) converge to x and y, respec
tively, there are N
1
and N
2
such that
x
n
−x < ε/2 for n ≥ N
1
and y
n
−y < ε/2 for n ≥ N
2
.
Consequently,
(x
n
+y
n
) −(x +y) = (x
n
−x) + (y
n
−y) ≤ x
n
−x +y
n
−y
≤ ε/2 +ε/2 = ε
for all n ≥ N = max{N
1
, N
2
}. Hence the sequence (x
n
+y
n
) converges and
lim(x
n
+y
n
) = limx
n
+ limy
n
, as claimed.
21
Note that above proposition holds true if instead of real sequences one
considers sequences in a normed space (X, ·). We call a real sequence (x
n
)
a null sequence if it converges to 0. That is, for every ε > 0, there is N ∈ N
such that x
n
 < ε for all n ≥ N.
Proposition 5.9. Let (x
n
) and (y
n
) be sequences in R.
(i) If (x
n
) is a null sequence and (y
n
) is a bounded sequence, then the
sequence (x
n
y
n
) is a null sequence.
(ii) If (x
n
) and (y
n
) are convergent sequences, then the sequence (x
n
y
n
)
converges and lim(x
n
y
n
) = limx
n
limy
n
.
(iii) If (x
n
) converges to x and x = 0, then almost all terms of (x
n
) are
nonzero and the sequence (1/x
n
) converges to 1/x.
Proof of (iI). Suppose that limx
n
= x and limy
n
= y. By (ii) of Proposi
tion 5.3, x
n
 ≤ A and y
n
 ≤ B for all n. Moreover, given ε > 0, there are
N
1
and N
2
so that
x
n
−x < ε/2(A+y) for n ≥ N
1
and y
n
−y < ε/2(A+y) for n ≥ N
2
.
Consequently,
(x
n
y
n
) −(xy) = x
n
(y
n
−y) +y(x
n
−x) ≤ x
n
 y
n
−y +y x
n
−x
≤ Ay
n
−y +y x
n
−x ≤ A
ε
2(A +y)
+y
ε
2(A +y)
= ε
for all n ≥ N = max{N
1
, N
2
}. Hence the sequence (x
n
y
n
) converges and
lim(x
n
y
n
) = limx
n
limy
n
, as claimed.
Proposition 5.10. (i) Let (x
n
) and (y
n
) be convergent sequences in R
and x
n
≤ y
n
for inﬁnitely many n. Then limx
n
≤ limy
n
.
(ii) Let (x
n
) and (y
n
) and (z
n
) be sequences in R and x
n
≤ y
n
≤ z
n
for
almost all n. If limx
n
= limz
n
= a, then (y
n
) converges to a.
Proof of (ii). Take ε > 0. Then here are N
1
and N
2
so that
x
n
−a < ε for n ≥ N
1
and z
n
−a < ε for n ≥ N
2
.
Hence
a −ε < x
n
< a +ε for n ≥ N
1
and a −ε < z
n
< a +ε for n ≥ N
2
22
and since x
n
≤ y
n
≤ z
n
,
a −ε < x
n
≤ y
n
≤ z
n
< a +ε
for all n ≥ N = max{N
1
, N
2
}. This means that y
n
−a < ε for all n ≥
N.
Deﬁnition 5.11. A sequence (x
n
) in R is increasing, if x
n
≤ x
n+1
for all
n ∈ N, and decreasing if x
n+1
≤ x
n
for all n ∈ N. If (x
n
) is either increasing
or decreasing, then it is called monotone.
Proposition 5.12. Every increasing (or decreasing) bounded sequence (x
n
)
in R converges,and
x
n
ր sup{x
n
 n ∈ N} ( or x
n
ց inf{x
n
 n ∈ N}).
Proof. Suppose that (x
n
) is increasing and Set a = sup{x
n
 n ∈ N} ∈ R. By
the characterization of the supremum,
(a) x
n
≤ a for all n.
(b) given ε, there is N such that a −ε < x
N
.
Since (x
n
) is increasing,
a −ε < x
N
≤ x
n
≤ a < a +ε
for all n ≥ N. Hence (x
n
) converges to x as claimed.
Example 5.13. Let a > 0 and α > 0. Deﬁne a sequence (x
n
) by setting x
0
= α
and
x
n+1
=
1
2
x
n
+
a
x
n
. (1)
We claim that the sequence (x
n
) converges to
√
a. To see this we shall show
that (x
n
) is bounded below by
√
a and it is decreasing. Consider the function
f(x) =
1
2
x +
a
x
for x > 0. Diﬀerentiating one ﬁnds that f
′
(x) =
1
2
1 −
a
x
2
< 0
for x ∈ (0,
√
a) and f
′
(x) > 0 for x ∈ (
√
a, ∞). Hence f takes its minimum at
a =
√
a and f(x) ≥ f(
√
a) =
√
a. So, x
n
≥
√
a for all n ≥ 1. Next
x
n
−x
n+1
= x
n
−
1
2
x
n
+
a
x
n
=
1
2
x
n
−
a
x
n
=
x
2
n
−a
2x
n
≥ 0
since x
2
n
≥ a. This means that x
n
≥ x
n+1
for all n ≥ 1 so that (x
n
) is decreasing.
Then the above proposition implies that x
n
→ x where x ≥
√
a > 0 Then also
x
n+1
→ x. So, taking limits in (1), we get
x =
1
2
x +
a
x
and solving for x one ﬁnds x =
√
a.
23
Proposition 5.14. Every sequence contains a monotone subsequence.
Proof. Consider a sequence (x
n
). We call the mth term x
m
a peak if
x
m
≥ x
n
for all n ≥ m. There are two cases to consider.
Case 1. There are inﬁnitely many peaks. List them according the in
creasing subscripts: x
n
1
, x
n
2
, . . .. Then, since each of them is a peak, we
have
x
n
1
≥ x
n
2
≥ x
n
3
≥ . . . .
Hence (x
n
k
) is a decreasing subsequence of (x
n
).
Case 2. There are ﬁnitely many peaks. List them according to the increas
ing x
m
1
, x
m
2
, . . . , x
m
l
. Then set n
1
= m
l
+ 1. The n
1
terms x
n
1
is not a
peak and so there is an index n
2
> n
1
such that x
n
1
< x
n
2
. The term x
n
2
is
also not a peak and there is n
3
> n
2
such that x
n
2
< x
n
3
. Continuing this
way we obtain a strictly increasing subsequence (x
n
k
) of (x
n
).
5.1.1 Inﬁnite limits
Deﬁnition 5.15. A sequence of real numbers (x
n
) converges to ∞, in sym
bols x
n
→ ∞ or limx
n
= ∞, if for every M > 0 there exists N such that
x
n
≥ M for all n ≥ N.
Similarly, (x
n
) converges to −∞, in symbols x
n
→ −∞ or limx
n
= −∞ if
for every M < 0 , there is there exists N such that
x
n
≤ M for all n ≥ N.
5.1.2 Some Special Sequences
(1) Let a ∈ R. Then
a
n
→ 0 if a < 1
a
n
diverges if a > 1
Suppose that a < 1. Then a =
1
1+h
for some h > 0. By the binomial theorem,
(1 +h)
n
=
n
¸
k=0
n
k
h
k
≥ nh
so that
0 ≤ a
n
 = a
n
=
1
(1 +h)
n
≤
1
nh
.
24
Since 1/nh → 0, a
n
→ 0 by the comparison test. Assume that a > 1. Then
a = 1 +h for some h and then
a
n
 = a
n
 = (1 +h)
n
≥ nh,
showing that (a
n
) is unbounded.
(2) Let k ∈ N and let a ∈ R be such that a > 1. Then
lim
n→∞
n
k
a
n
= 0.
To see this write a = 1 +h where h > 0 and apply the binomial theorem,
a
n
= (1 +h)
n
=
n
¸
m=0
n
m
h
m
≥
n
k + 1
h
k+1
≥
n(n −1) · · · (n −k)
(k + 1)!
h
k+1
.
So,
0 ≤
n
k
a
k
≤
(k + 1)!n
k
h
k+1
n(n −1) · · · (n −k)
and the claimed follows using the comparison since the right hand side converges
to 0 as n → ∞.
(3) For all a ∈ R,
lim
n→∞
a
n
n!
= 0.
(4) lim
n→∞
n
√
n = 1.
To see this write
n
√
n = 1 +a
n
with a
n
≥ 0 (since it is easy to see that
n
√
n ≥ 1. So,
(1 +a
n
)
n
= n.
By the binomial theorem,
n = (1 +a
n
)
n
= 1 +
n
1
a
n
+
n
2
a
2
n
+. . . ≥ 1 +
n
2
a
2
n
= 1 +
n(n −1)
2
a
2
n
.
From this we get
0 ≤ a
2
n
≤
2
n
, i.e., 0 ≤
n
√
n −1 = a
n
≤
2/n
which by comparison implies that
n
√
n → 1.
(5) For all a > 0, lim
n→∞
n
√
a = 1.
If a = 1, then there is nothing to prove. If a > 1, then
1
n
√
a ≤
n
√
n
which implies that (
n
√
a) converges to 1. So, assume that 0 < a < 1, then 1/a > 1
so that
n
1/a → 1. Since
n
√
a = 1/
n
1/a, the claim follows.
25
5.1.3 The limit superior and limit inferior
Let (x
n
) be a bounded sequence. For each n ∈ N, let
y
n
= sup
m≥n
x
m
= sup{x
n
, x
n+1
, . . .}.
Then {y
n
} is decreasing, and it is bounded since (x
n
) is bounded. By Proposition
5.12, (y
n
) converges. The limit is called upper limit of (x
n
), and is denoted by
limsup x
n
. Similarly, let z
n
= inf
m≥n
x
m
= inf{x
n
, x
n+1
, . . .}. Then (z
n
) is in
creasing, and it is bounded since (x
n
) is bounded. The limit of (z
n
) is called lower
limit of (x
n
), and is denoted by liminf x
n
. If (x
n
) is not bounded from above, then
its upper limit is equal to ∞ and if (x
n
) is not bounded from below, then its lower
limit is equal to −∞. Summarizing
limsup x
n
= limx
n
= inf
n≥m
sup
k≥n
x
k
= lim
n→∞
sup
k≥n
x
k
liminf x
n
= limx
n
= sup
n≥m
inf
k≥n
x
k
= lim
n→∞
inf
k≥n
x
k
.
The basic properties of the upper and the lower limits are listed in the following
proposition:
Proposition 5.16. If (x
n
) and (y
n
) are sequences of real numbers, then:
(a) limsup(−x
n
) = −liminf x
n
and liminf(−x
n
) = −limsupx
n
.
(c) limsup(ax
n
) = a limsupx
n
and liminf(ax
n
) = a liminf x
n
for any a > 0.
(d) limsup(x
n
+y
n
) ≤ limsup x
n
+limsupy
n
and liminf x
n
+liminf y
n
≤ liminf(x
n
+
y
n
).
(e) liminf x
n
≤ limsup x
n
, with equality if and only if (x
n
) converges. In this
case limsup x
n
= limx
n
.
Theorem 5.17 (BolzanoWeierstrass Theorem).
Let (x
n
) be a bounded sequence in R. Then (x
n
) has convergent subsequence.
Proof. By Proposition 5.14, (x
n
) has a monotone subsequence (x
n
k
). Since (x
n
k
)
is bounded, Proposition 5.12 implies that is converges.
Theorem 5.18 (Cauchy’s criterion). A sequence (x
n
) of real numbers converges
if and only if (x
n
) is a Cauchy sequence.
Proof. We already know that a convergent sequence is Cauchy (Proposition 5.7).
Hence we have to prove that a Cauchy sequence (x
n
) converges to some x ∈ R. By
Proposition 5.7, (x
n
) is bounded so that by Theorem 5.17, it contains a convergent
subsequence, say x
n
k
→ x. We claim that x
n
→ x. To see this, take ε > 0. Then
there is K such that
x
n
k
−x < ε/2 for all k ≥ K.
26
Moreover, since (x
n
) is Cauchy, there is N such that
x
n
−x
m
 < ε/2 for all n, m ≥ N.
Take k such that n
k
≥ N and let n ≥ N. Then
x
n
−x ≤ x
n
−x
n
k
 +x
n
k
−x < ε/2 +ε/2 = ε.
Hence (x
n
) converges to x, as claimed.
Example 5.19. Deﬁne (x
n
) by setting x
1
= 1, x
2
= 2, and
x
n
=
1
2
(x
n−1
+x
n−2
) .
We claim that the sequence converges to x = 5/3. To see this we shall show that
(x
n
) is Cauchy and that the subsequence (x
2n+1
) converges to x = 5/3. First note
that 1 ≤ x
n
≤ 2 for all n. Next
x
n
−x
n+1
 =
1
2
n−1
.
Indeed, for n = 1, x
1
−x
2
 = 1 =
1
2
0
. Assuming that x
n
−x
n+1
 =
1
2
n−1
, we show
that x
n+1
−x
n+2
 =
1
2
n
. We have
x
n+1
−x
n+2
 =
x
n+1
−
1
2
(x
n+1
−x
n
)
=
1
2
x
n
−x
n+1
 =
1
2
n
,
as claimed. Consequently, if m > n,
x
n
−x
m
 ≤ x
n
−x
n+1
 +x
n+1
−x
n+2
 +. . . +x
m−1
−x
m

≤
1
2
n−1
+
1
2
n
+. . . +
1
2
m−2
=
1
2
n−1
1 +
1
2
+. . . +
1
2
m−n−1
<
1
2
n−2
and since 1/2
n−2
→ 0, it follows that indeed (x
n
) is Cauchy. Now to ﬁnd the limit
of x we ﬁrst show that x
2n−1
< x
2n
. This holds true for n = 1. Assuming that
x
2n−1
< x
2n
, we show that x
2n+1
< x
2n+2
. From the assumption if follows that
x
2n−1
<
1
2
(x
2n
+x
2n−1
) < x
2n
.
So, x
2n−1
< x
2n+1
and
x
2n+2
=
1
2
(x
2n+1
+x
2n
) >
1
2
(x
2n−1
+x
2n
) = x
2n+1
,
as claimed. From this and x
2n+1
−x
n+2
 = 1/2
2n
, it follows that
x
2n+2
= x
2n+1
+
1
2
2n
.
27
Now use induction to prove that
x
2n+1
= 1 +
1
2
+
1
2
3
+. . . +
1
2
2n−1
.
For n = 1 this is clear. Assuming the above equality we show that x
2n+3
=
1 +
1
2
+
1
2
3
+. . . +
1
2
2n+1
. We have
x
2n+3
=
1
2
(x
2n+2
+x
2n+1
) =
1
2
1
2
2n
+ 2x
2n+1
= 1 +
1
2
+
1
2
3
+. . . +
1
2
2n−1
+
1
2
2n+1
,
as claimed. Now, note that
x
2n+1
= 1 +
1
2
+
1
2
3
+. . . +
1
2
2n−1
= 1 +
1
2
1 +
1
2
2
+
1
2
4
+. . . +
1
2
2n−2
= 1 +
1
2
1 +
1
4
+
1
4
2
+. . . +
1
4
n−1
= 1 +
2
3
1 −
1
4
n
→
5
3
,
where we have used the formula
¸
n
k=0
a
k
=
1−a
n+1
1−a
provided that a = 1.
28
xm ) ≤ ε for all n. x) < ε/2 for all n ≥ N. 5. nk ≥ k for all k ∈ N. If (xn ) is a convergent sequence with limit x.. Let (X.8. xm ) < ε/2 + ε/2 = ε for all n. (xn + yn ) − (x + y) = (xn − x) + (yn − y) ≤ xn − x + yn − y ≤ ε/2 + ε/2 = ε for all n ≥ N = max{N1 .5. Hence d(xn .1 Real sequences Proposition 5. Proof of (i). Proof. (i) Every Cauchy sequence is bounded. x) + d(x. m ≥ N. there is N such that d(xn . Deﬁnition 5. (xn ) is a Cauchy sequence as claimed. given ε > 0. Take a neighborhood U of x. respectively. nk ≥ N for all k ≥ N .Proposition 5. (ii) Every convergent sequence in X is Cauchy. Then. . there are N1 and N2 such that xn − x < ε/2 Consequently. Thus xnk ∈ U for all k ≥ N . Then (i) The sequence (xn + yn ) converges and lim(xn + yn ) = lim xn + lim yn . there is N ∈ N such that xn ∈ U for all n ≥ N . d) be a metric space. Since (xn ) and (yn ) converge to x and y. (ii) The sequence (αxn ) converges and lim(αxn ) = α lim xn . Let (xn ) and (yn ) be convergent sequences in R and let α ∈ R. Let (xnk ) be a subsequence of (xn ). Proposition 5. as claimed. So. m ≥ N .6. Assume that (xn ) converges to x. N2 }. Since lim xn = x. Proof of (ii). From the deﬁnition of a subsequence. d) is said to be Cauchy if for every ε > 0. So. A sequence (xn ) in a metric space (X. Take ε > 0. Hence (xnk ) converges to x as claimed. 21 for n ≥ N1 and yn − y < ε/2 for n ≥ N2 . xm ) ≤ d(xn .7. then every subsequence (xnk ) of (xn ) converges to x. Hence the sequence (xn + yn ) converges and lim(xn + yn ) = lim xn + lim yn . there exists N such that d(xn .
xn  ≤ A and yn  ≤ B for all n. Then lim xn ≤ lim yn . If lim xn = lim zn = a. Take ε > 0. and yn − y < ε/2(A+y) for n ≥ N2 . . We call a real sequence (xn ) a null sequence if it converges to 0. (iii) If (xn ) converges to x and x = 0.10. (ii) If (xn ) and (yn ) are convergent sequences. then the sequence (xn yn ) converges and lim(xn yn ) = lim xn lim yn . there are N1 and N2 so that xn − x < ε/2(A+y) for n ≥ N1 Consequently. By (ii) of Proposition 5. Proposition 5.3. then almost all terms of (xn ) are nonzero and the sequence (1/xn ) converges to 1/x. That is. (i) If (xn ) is a null sequence and (yn ) is a bounded sequence. Suppose that lim xn = x and lim yn = y. Proof of (ii). Hence the sequence (xn yn ) converges and lim(xn yn ) = lim xn lim yn . Proof of (iI). then (yn ) converges to a. for every ε > 0. N2 }. Let (xn ) and (yn ) be sequences in R. (xn yn ) − (xy) = xn (yn − y) + y(xn − x) ≤ xn  yn − y + y xn − x ε ε + y =ε ≤ A yn − y + y xn − x ≤ A 2(A + y) 2(A + y) for all n ≥ N = max{N1 . (ii) Let (xn ) and (yn ) and (zn ) be sequences in R and xn ≤ yn ≤ zn for almost all n.Note that above proposition holds true if instead of real sequences one considers sequences in a normed space (X.9. Proposition 5. there is N ∈ N such that xn  < ε for all n ≥ N . Moreover. (i) Let (xn ) and (yn ) be convergent sequences in R and xn ≤ yn for inﬁnitely many n. then the sequence (xn yn ) is a null sequence. Then here are N1 and N2 so that xn − a < ε for n ≥ N1 Hence a − ε < xn < a + ε for n ≥ N1 and a − ε < zn < a + ε for n ≥ N2 22 and zn − a < ε for n ≥ N2 . · ). given ε > 0. as claimed.
Suppose that (xn ) is increasing and Set a = sup{xn  n ∈ N} ∈ R. taking limits in (1).and since xn ≤ yn ≤ zn . Next xn − xn+1 = xn − 1 2 xn + a xn = 1 2 xn − a xn = x2 − a n ≥0 2xn since x2 ≥ a. Let a > 0 and α > 0. N2 }. Since (xn ) is increasing. Deﬁnition 5. 1 a x+ 2 x 23 . (x n Then the above proposition implies that xn → x where x ≥ a > 0 Then also xn+1 → x. ∞). By the characterization of the supremum. then it is called monotone. To see this we shall show ) that (xn ) is bounded below by a and it is decreasing. So. (1) √ We claim that the sequence (xn√ converges to a. if xn ≤ xn+1 for all n ∈ N. we get x= and solving for x one ﬁnds x = √ a. a) and f√ > √ for x ∈ ( a.12. Every increasing (or decreasing) bounded sequence (xn ) in R converges. Proposition 5. Deﬁne a sequence (xn ) by setting x0 = α and xn+1 = 1 2 xn + a xn . a − ε < xN ≤ xn ≤ a < a + ε for all n ≥ N . and decreasing if xn+1 ≤ xn for all n ∈ N. (a) xn ≤ a for all n. (b) given ε. If (xn ) is either increasing or decreasing. xn ≥ a for all n ≥ 1. a − ε < xn ≤ yn ≤ zn < a + ε for all n ≥ N = max{N1 . Consider the function a +a f (x) = 1 x√ x for x > 0. This means that yn − a < ε for all n ≥ N. This means that xn ≥ xn+1 for all n ≥ 1 so that √ n ) is decreasing. Proof. Example 5.13.11.and xn ր sup{xn  n ∈ N} ( or xn ց inf{xn  n ∈ N}). Diﬀerentiating one ﬁnds that f ′ (x) = 1 1 − x2 < 0 2 2 √ ′ for x ∈ (0. there is N such that a − ε < xN . Hence (xn ) converges to x as claimed. Hence f takes its minimum at (x) 0 √ √ a = a and f (x) ≥ f ( a) = a. So. A sequence (xn ) in R is increasing.
There are two cases to consider.2 Some Special Sequences for all n ≥ N . . in symbols xn → −∞ or lim xn = −∞ if for every M < 0 . xm2 . Then.14. . xn2 . xml . Similarly. . There are inﬁnitely many peaks. Then an diverges Suppose that a < 1. . if for every M > 0 there exists N such that xn ≥ M for all n ≥ N . List them according to the increasing xm1 . we have xn 1 ≥ xn 2 ≥ xn 3 ≥ .1.1 Inﬁnite limits Deﬁnition 5. Hence (xnk ) is a decreasing subsequence of (xn ). Case 1. Consider a sequence (xn ). in symbols xn → ∞ or lim xn = ∞. Then a = 1 1+h an → 0 if a < 1 if a > 1 for some h > 0. . The term xn2 is also not a peak and there is n3 > n2 such that xn2 < xn3 . .15. There are ﬁnitely many peaks..Proposition 5. n (1 + h)n = k=0 n k h ≥ nh k 1 1 ≤ . Every sequence contains a monotone subsequence. (1 + h)n nh so that 0 ≤ an  = a = n 24 . By the binomial theorem.1. Continuing this way we obtain a strictly increasing subsequence (xnk ) of (xn ). . (1) Let a ∈ R. The n1 terms xn1 is not a peak and so there is an index n2 > n1 such that xn1 < xn2 . . 5. Proof. Case 2. . Then set n1 = ml + 1. We call the mth term xm a peak if xm ≥ xn for all n ≥ m. A sequence of real numbers (xn ) converges to ∞. (xn ) converges to −∞. since each of them is a peak. there is there exists N such that xn ≤ M 5. . List them according the increasing subscripts: xn1 .
n a = (1 + h) = m=0 n n n m h ≥ m n n(n − 1) · · · (n − k) k+1 h . lim n→∞ n! √ (4) limn→∞ n n = 1. showing that (an ) is unbounded. 0≤ nk (k + 1)!nk ≤ k+1 k a h n(n − 1) · · · (n − k) and the claimed follows using the comparison since the right hand side converges to 0 as n → ∞. If a = 1. then √ √ 1na≤ nn √ which implies that ( n a) converges to 1. . hk+1 ≥ (k + 1)! k+1 So. Then nk = 0. the claim follows. an → 0 by the comparison test. n→∞ an lim To see this write a = 1 + h where h > 0 and apply the binomial theorem. an + an + . If a > 1.. limn→∞ a = 1. then 1/a > 1 √ so that n 1/a → 1. an = 0.Since 1/nh → 0. . (2) Let k ∈ N and let a ∈ R be such that a > 1. 25 . (3) For all a ∈ R. Assume that a > 1. So. √ √ To see this write n n = 1 + an with an ≥ 0 (since it is easy to see that n n ≥ 1. ≥ 1 + an = 1 + 2 1 2 2 √ which by comparison implies that n n → 1. Then a = 1 + h for some h and then an  = an  = (1 + h)n ≥ nh. 0 ≤ √ n n − 1 = an ≤ 2/n n n 2 n(n − 1) 2 n 2 an .e. By the binomial theorem. (1 + an )n = n. Since n a = 1/ n 1/a. n = (1 + an )n = 1 + From this we get 0 ≤ a2 ≤ n 2 . n i. So. assume that 0 < a < 1. then there is nothing to prove. √ n (5) For all a > 0.
.7).18 (Cauchy’s criterion). 26 . Since (xnk ) is bounded. If (xn ) and (yn ) are sequences of real numbers. We already know that a convergent sequence is Cauchy (Proposition 5.12 implies that is converges.1. The limit is called upper limit of (xn ).3 The limit superior and limit inferior Let (xn ) be a bounded sequence. For each n ∈ N. and it is bounded since (xn ) is bounded. Theorem 5. . then: (a) lim sup(−xn ) = − lim inf xn and lim inf(−xn ) = − lim sup xn . By Proposition 5.}. Theorem 5. . and is denoted by lim inf xn . Proposition 5. To see this. Then (xn ) has convergent subsequence.17. say xnk → x. Hence we have to prove that a Cauchy sequence (xn ) converges to some x ∈ R. By Proposition 5.14.12.17 (BolzanoWeierstrass Theorem). (c) lim sup(axn ) = a lim sup xn and lim inf(axn ) = a lim inf xn for any a > 0.7. . Proof. Summarizing lim sup xn = lim xn = inf sup xk = lim sup xk n≥m k≥n n→∞ k≥n lim inf xn = lim xn = sup inf xk = lim inf xk . Proof. let yn = sup xm = sup{xn . We claim that xn → x. xn+1 . . and it is bounded since (xn ) is bounded. n≥m k≥n n→∞ k≥n The basic properties of the upper and the lower limits are listed in the following proposition: Proposition 5. xn+1 . m≥n Then {yn } is decreasing. take ε > 0.5. Similarly. (xn ) is bounded so that by Theorem 5. (xn ) has a monotone subsequence (xnk ). then its lower limit is equal to −∞. A sequence (xn ) of real numbers converges if and only if (xn ) is a Cauchy sequence. with equality if and only if (xn ) converges. Then (zn ) is increasing. then its upper limit is equal to ∞ and if (xn ) is not bounded from below. If (xn ) is not bounded from above. By Proposition 5. Then there is K such that xnk − x < ε/2 for all k ≥ K. let zn = inf m≥n xm = inf{xn . it contains a convergent subsequence.}. (e) lim inf xn ≤ lim sup xn . (d) lim sup(xn +yn ) ≤ lim sup xn +lim sup yn and lim inf xn +lim inf yn ≤ lim inf(xn + yn ). and is denoted by lim sup xn .16. . (yn ) converges. In this case lim sup xn = lim xn . The limit of (zn ) is called lower limit of (xn ). Let (xn ) be a bounded sequence in R.
+ m−n−1 < n−2 2 2 2 2 and since 1/2n−2 → 0. . xn − xm  ≤ xn − xn+1  + xn+1 − xn+2  + . we show that x2n+1 < x2n+2 . it follows that x2n+2 = x2n+1 + 1 . Hence (xn ) converges to x. From this and x2n+1 − xn+2  = 1/22n . 22n 27 . Take k such that nk ≥ N and let n ≥ N . 2 2 2 as claimed.Moreover. Deﬁne (xn ) by setting x1 = 1. as claimed. it follows that indeed (xn ) is Cauchy. . x1 − x2  = 1 = 20 . + xm−1 − xm  1 1 1 ≤ n−1 + n + . . x2 = 2. To see this we shall show that (xn ) is Cauchy and that the subsequence (x2n+1 ) converges to x = 5/3. + m−2 2 2 2 1 1 1 1 = n−1 1 + + . From the assumption if follows that x2n−1 < So. Then xn − x ≤ xn − xnk  + xnk − x < ε/2 + ε/2 = ε. if m > n. First note that 1 ≤ xn ≤ 2 for all n. . Assuming that x2n−1 < x2n . Example 5. 2 as claimed. 2 2 1 (x2n + x2n−1 ) < x2n . 1 Indeed. 2n−1 1 2n−1 . Assuming that xn − xn+1  = that xn+1 − xn+2  = 21 . Next xn − xn+1  = 1 . Now to ﬁnd the limit of x we ﬁrst show that x2n−1 < x2n . x2n−1 < x2n+1 and x2n+2 = 1 1 (x2n+1 + x2n ) > (x2n−1 + x2n ) = x2n+1 . for n = 1. m ≥ N . . .19. Consequently. 2 We claim that the sequence converges to x = 5/3. there is N such that xn − xm  < ε/2 for all n. since (xn ) is Cauchy. and xn = 1 (xn−1 + xn−2 ) . We have n we show 1 1 1 xn+1 − xn+2  = xn+1 − (xn+1 − xn ) = xn − xn+1  = n . This holds true for n = 1.
=1+ 3 4 3 n k=0 where we have used the formula ak = 1−an+1 1−a provided that a = 1. . . . . + 22n+1 . . . + 2n−1 . . . 28 .Now use induction to prove that x2n+1 = 1 + 1 1 1 + . + 2n−1 2 2 2 1 1 1 1 1 + 2 + 4 + . 2 2 2 2 as claimed. + 2n−1 + 2n+1 . + 2 23 2 For n = 1 this is clear. note that x2n+1 = 1 + 1 1 1 + 3 + . Assuming the above equality we show that x2n+3 = 1 1 1 1 + 2 + 23 + . . We have x2n+3 = 1 1 1 + 2x2n+1 (x2n+2 + x2n+1 ) = 2 2 22n 1 1 1 1 = 1 + + 3 + . . Now. . . + n−1 =1+ 2 4 4 4 1 5 2 1− n → . + 2n−2 =1+ 2 2 2 2 1 1 1 1 1 + + 2 + .